Study of associativity in MSMEs in the province of Imbabura-Ecuador, a case study of manufacturing industries. (Innovation & Development in Engineering and Applied Science, 2025)
The research carried out on MSMEs in the province of Imbabura through the application of a survey focused on knowing if MSMEs are aware of associativity and the benefits it generates, seeks to identify if companies are interested in managing an associative consortium model based on the economic sector in which they are classified according to the work activity carried out, for this the research was divided into phases. Phase I. identification of the population and selection of the sample using statistical formulas and a greater number of companies according to the economic sector and canton, obtaining a sample of 328 for the purposes of this investigation, phase II, information gathering was carried out through the application of a survey where information was collected about the strategic planning managed in each MSME and it was identified that a low number of companies have a strategic planning and organizational structure, phase III, with the purpose of analyzing whether companies are interested in forming associative consortia, six questions were developed, from which it was obtained that there is a lack of knowledge of the benefits that an associative consortium provides and that they are interested in managing activities to improve their positioning. both nationally and internationally
Keywords: Associativity; MIPYMES; Consortiums; Strategic planning